FIBONACCI SEQUENCE AND ORDERLINESS AS OBSERVED IN THE CREATIONS OF ALLAH - Saifuddeen, Shaikh Mohd; Masran, Mohd Rezuan (Online Journal of Research in Islamic Studies, 2017)
There are numerous verses in the Quran that encourage Muslims to observe the many creations of Allah. This article is an exploratory discussion on the observation of a sequence of numbers known as the Fibonacci sequence (also known as the Fibonacci numbers) which can be observed in the creations of Allah. The history of Fibonacci sequence dated back to 1202 in the magnum opus of the Italian mathematician, Leonardo Pisano Fibonacci, entitled Liber Abaci (Book of Calculation). This article discusses verses in the Quran that encourage us to observe Allah?s creations. There are many occurrences of the Fibonacci sequence in the animal and plant kingdoms, for example in the sunflower florets, ram?s horn, spiralling shell, etc. This article will shed light on three occurrences, namely: (i) Structure of the coronary arterial tree; (ii) Branching of leaves; and, (iii) Seed distribution of flowers and conifers. From this article, it will be evident that the abundance of verses in the Quran that encourage mankind to observe the nature as a sign of Allah?s existence and His Might in creating the world in such a perfect and orderly manner. One of such beauty is manifested in the sequence of Fibonacci sequence that can be easily observed in our surroundings.